Reparation and reconciliation : the rise and fall of integrated higher education - Smith, Christi Michelle (University of North Carolina Press, 2016)
"This is the first book to reveal the nineteenth-century struggle for racial integration on U.S. college campuses. As the Civil War ended, the need to heal the scars of slavery, expand the middle class, and reunite the nation engendered a dramatic interest in higher education by policy makers, voluntary associations, and African Americans more broadly. Formed in 1846 by Protestant abolitionists, the American Missionary Association united a network of colleges open to all, designed especially to educate African American and white students together, both male and female. Case studies at three colleges--Berea College, Oberlin College, and Howard University--reveal the strategies administrators used and the challenges they faced as higher education quickly developed as a competitive social field"--